(untitled) (Bulletin of Innovative Research, 2026)
This article analyzes manipulative strategies implemented through the widely used “we” and “they” opposition in discourse from a pragmatic perspective. The study examines the communicative functions of this opposition in political, social, and mass media discourses, the mechanisms of psychological influence on the target audience, as well as its connection with speech acts. In addition, the process of constructing positive identification through the concept of “we” and forming a negative image through the concept of “they” is explained from the standpoint of pragmatic factors. The findings of the study are of significant theoretical and practical importance for identifying and analyzing manipulative discourse.